1994
DOI: 10.1111/j.1558-5646.1994.tb01363.x
|View full text |Cite
|
Sign up to set email alerts
|

THE RELATIONSHIP BETWEEN INBREEDING DEPRESSION AND PRIOR INBREEDING AMONG POPULATIONS OF FOURMIMULUSTAXA

Abstract: Abstract.-When recessive mutations are the primary cause of inbreeding depression, a negative relationship betweenthe levelsof prior inbreeding and inbreeding depression is expected. We tested this prediction using 15 populations chosen a priori to represent a wide range of prior inbreeding among four closely related taxa of the Mimulus guttatus species complex. Artificially selfed and outcrossed progeny were grown under controlled growth-chamber conditions, and inbreeding depression was estimated for each pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 55 publications
3
83
0
Order By: Relevance
“…In fact, for the self/near comparisons we observed slightly, but nonsignificantly, higher inbreeding depression in hermaphrodite lineages than in female lineages, Although Husband and Schemske's (1996) review of inbreeding depression in 54 species revealed a significant negative correlation between inbreeding and inbreeding depression, several studies in addition to ours have shown a weak correlation or no correlation, suggesting that the relationship is a complicated one. For example, a significant correlation between prior inbreeding and inbreeding depression in several taxa of the Mimulus guttatus species complex only existed for one of the five fitness traits measured (Latta and Ritland 1994). Holtsford (1996) found that cumulative inbreeding depression measured at the end of flowering was not significantly different for populations of Clarkia tembloriensis that varied significantly in their inbreeding coefficients.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…In fact, for the self/near comparisons we observed slightly, but nonsignificantly, higher inbreeding depression in hermaphrodite lineages than in female lineages, Although Husband and Schemske's (1996) review of inbreeding depression in 54 species revealed a significant negative correlation between inbreeding and inbreeding depression, several studies in addition to ours have shown a weak correlation or no correlation, suggesting that the relationship is a complicated one. For example, a significant correlation between prior inbreeding and inbreeding depression in several taxa of the Mimulus guttatus species complex only existed for one of the five fitness traits measured (Latta and Ritland 1994). Holtsford (1996) found that cumulative inbreeding depression measured at the end of flowering was not significantly different for populations of Clarkia tembloriensis that varied significantly in their inbreeding coefficients.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…In a study of three populations of Clarkia tembloriensis with selfing rates ranging from 42% to 97%, Holtsford and Ellstrand (1990) found some evidence for a negative relationship in some reproductive characters. Latta and Ritland (1994) investigated the relationship between inbreeding depression and the inbreeding coefficient (rather than the selfing rate) in Mimulus taxa. The relationship was negative for all five traits related to fitness, but significantly so for only one trait.…”
Section: Relation Of Data To Theory Based On Mutation-selection Balancementioning
confidence: 99%
“…Its magnitude in natural populations differs greatly among species and sometimes among populations within species. This variation, both in severity of depression and in its ontogenetic timing, has been related to differences in the mating system, particularly the degree of selfing (Charlesworth and Charlesworth 1987;Lande et al 1994;Latta and Ritland 1994;Parker et al 1995;Husband and Schemske 1996). The review by Husband and Schemske (1996) is recent and thorough, and the reader is referred to it for details.…”
mentioning
confidence: 99%